Towards a Sustainable Horticultural Value Chain among Smallholder farmers in Kenya: Unlocking the Potential of Mobile Telephone - Musau , Enock G. (African Journal of Education,Science and Technology (AJEST), 2021)
Sustainable agriculture is fast emerging as a paradigm that seeks to ensure that farming is done in a manner that meets today’s society’s food needs while taking cognizance of future generation’s needs. The Big Four Agenda clearly underscores the need for food security for all Kenyans. This paper explores the potential contributions that mobile phone services can make towards sustenance of the horticultural value chain among smallholder horticultural farmers. The paper outlines findings from an external online desk review of studies that have attempted to analyze the role of ICT functionality in agriculture and particularly from a smallholder farmer perspective. Studies were sourced on-line under the criteria that they focused on the agricultural value chain, and were carried out from the year 2010 to date. From the reviews, the paper concludes that mobile telephone usage is fast penetrating the agricultural industry, and provides potential for improving the horticultural value chain. Among the potential benefits that could accrue from mobile usage includes; creation and capture of value across the chain, access to agricultural information, improved efficiency in the value chain, and enhanced access to markets. However, relying on the secondary data approach alone makes the findings to be questionable in terms of authenticity and representatives. Future studies should strive to be causal in nature and should rely on primary data sources.